Engineering the Guitar - French, Richard Mark (Springer, 2017)
Engineering the Guitar: Theory and Practice uniquely describes the mechanics of the guitar for engineers and craftsmen alike. Complete with informative illustrations, this popular musical volume describes the underlying mechanical concepts behind the guitar, supported by theory and test. A detailed description of guitar electronics, paired with an in-depth analysis of sound quality, appeals to scientific audiences as well as musicians technically apt. Readers will gain an understanding of the technical behavior of the instrument with respect to structural and component dynamics, in addition to the informative treatment of analytical models. Hand made and mass produced techniques are also examined in a chapter devoted to manufacturing processes. Audiences interested in mechanics, acoustics, and instrument making will find Engineering the Guitar: Theory and Practice an informative and enjoyable read.